THE PROPERTY OF CHILD – MANAGING, USE AND DISPOSAL - Vagner-Ličenoski, Sofija (Law - Theory and Practice, 2006)
The child is every minor who did not acquire full active legal capacity before the majority. Parents have the right and duty at the same time to be the lawful representatives of their child entering into all transactions of property aquisition. They can also represent their child on the base of contract in all the transactions that child can enter into on the ground of it’s active legal capacity. The child who did not reach the age of fourteen is able to carry out by itself only the transactions for acquiring rights (donatio, commodatum), not obligations. It may carry out the the usual daily transactions too. The child who reached the age of fourteen can enter into all other transactions with the consent of it’s parents. When the object of transaction is movable property of great value or real estate, the permission of the welfare comitee is necessary for validity of such transaction. The 15-year-old child aquires the working capacity and capability of free managing and disposal of the property aquired by the work. The parents manage and dispose of the property not acquired by the child’s work and of the property acquired by the work of the child who did not reach the age of fifteen. Adoptive parent has the same rights as parent on this matter. If a child is in guardianship, the custodian needs the consent of the welfare comitee for the transactions beyond the ordinary managing of protégé’s property and for the transactions of protégé’s property disposal. Established fostering does not influence on the parent rights and duties to manage and dispose of the child’s property.